Penanggulangan Infeksi Soil Transmitted Helminths di RW 9 Kel. Jatiwarna, Kec. Pondok Melati, Kota Bekasi - Heru Setiawan; Husjain Djajaningrat (IFI cabang Kota Bekasi, 2023)
STH infection is still a serious health problem that mainly occurs in school-age children. The main risk factors for the spread of this disease are unhealthy lifestyles and poor environmental sanitation. Therefore, it is necessary to have a program to increase knowledge, awareness, attitude, and behavior of people to live healthier and continue to maintain environmental sanitation and hygiene so that the spread of STH infection can be prevented. This community service program is carried out as part of the STH infection control program. The subjects of this program are preschool and school-age children and their parents in RW 9 Jatiwarna, Pondok Melati, Bekasi. The program consists of three parts: health education; identification of health knowledge, attitudes, and behaviors; and early detection of STH infection. As a result, most of the respondents have knowledge about STH infection in the moderate category, but most of them have good attitudes and behaviors for healthy living. Based on the results of laboratory tests, three (10 percent) school-age children were identified as positive for STH. Further medical examinations and treatment are required for school-age children who are based on a positive STH laboratory examination. In addition, the Bekasi City Health Office and Jatiwarna Health Center need to continue to carry out STH infection control programs in communities in Jatiwarna, Pondok Melati, Bekasi in an integrated and sustainable manner. Keywords: Knowledge, Attitudes, Healthy Living Practices and Incidence of Worms.